Methods of state support of real estate market and its classification - O. P. Kuznetsova; D. Yu. Smirnov; V. V. Kuznetsov (Омский научный вестник: Серия "Общество. История. Современность")
The state supports the real estate market not only during the economic crisis, but in all phases of the economic cycle. As a result the state simultaneously solves tasks of providing housing to the population, the expansion of the banking sector through the growth of mortgage loans and the increase of the stock market capitalization through the issuance of mortgage-backed securities, but not only anti-crisis stimulation of the construction industry. Classification of methods of state support of the real estate market allows to identify the compliance of a method to the phase of the economic cycle and, thereby, increase the efficiency of its practical use